Association of weight-adjusted waist index (WWI) and a body shape index (ABSI) with serum neurofilament light chain levels in a national study of U.S. adults - Zixuan Yan; Qingxin Gu; Hong Yin; Mingliang Yi; Xiao Wang; Ruirui Sun; Fanrong Liang; Dingjun Cai; Wenchuan Qi (Eating and Weight Disorders)
Abstract Objective This study explored how the weight-adjusted waist index (WWI) and a body shape index (ABSI) are related to serum neurofilament light chain (sNfL) levels among U.S. adults. We aimed to evaluate sNfL, which plays key roles in neuronal injury in neurological diseases, given its understudied connection to obesity. Methods We used cross-sectional data from the 2013–2014 National Health and Nutrition Examination Survey (NHANES) of people with complete information on the weight-adjusted waist index (WWI), a body shape index (ABSI), and serum neurofilament light chain (sNfL). Multiple linear regression analysis allowed us to investigate the separate connections among the WWI, ABSI, and sNfL. Moreover, interaction testing and subgroup analysis were performed to improve the general validity of our results. To assess any nonlinear correlations, we also performed threshold effect analysis and smoothed curve fitting. Results WWI and ABSI were positively linked with sNfL (WWI: β = 0.05, 95% CI 0.01–0.09; ABSI: β = 1.65, 95% CI 3.53–13.72). There was no clear reliance on this association according to subgroup analysis and interaction tests. Smoothed curve fitting and saturation effects also demonstrated nonlinear associations between WWI and ABSI and sNfL, with inflection points of 10.38 and 0.38, respectively. Conclusion In the adult American population, while the WWI and ABSI are linearly positively correlated with serum neurofilament light protein (sNfL), the effect size is greater for the ABSI. This correlation provides fresh evidence connecting obesity to neurological conditions, deepening our comprehension of the extensive health impacts associated with obesity. Level of Evidence Level I, experimental studies.